2014
DOI: 10.1038/nrm3919
|View full text |Cite
|
Sign up to set email alerts
|

Protein neddylation: beyond cullin–RING ligases

Abstract: NEDD8 is a ubiquitin-like protein that activates the largest ubiquitin E3 ligase family, the cullin RING ligases. Many non-cullin neddylation targets have been proposed in recent years. However, overexpression of exogenous NEDD8 can trigger NEDD8 conjugation through the ubiquitylation machinery, which makes validating potential NEDD8 targets challenging. Here we re-evaluate these studies in light of the current understanding of the neddylation pathway, and suggest criteria for the identification of genuine ned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
526
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(536 citation statements)
references
References 178 publications
(256 reference statements)
9
526
0
1
Order By: Relevance
“…E1 (NAE), E2 (UbCH12), E3 // IsopepƟdase [40,41] Others UBLs: ATG12, FAT10, MNSFβ, UFM1, URM, UBL5, SUMO4 [34][35][36][37][38] ModificaƟon of Ub: Phospho-Ub and Acetyl-Ub PolyubiquiƟn chains: Branched chains PolyUb mixed chains (modified by SUMO, NEDD8, ISG15) [21][22][23][24][25] Nucleo Ɵdes [190,191] Poly (PARylaƟon) Glu Asp Poly(ADP-ribose)polymerases (PARPs) // Poly (ADP-ribose) glycohydrolase (PARG) [191] * Found in prokaryotes A Almost followed by a proline (1 [39,40]. NEDD8 also forms chains through one of its six Lys [41].…”
Section: Pdb: 1nddmentioning
confidence: 99%
“…E1 (NAE), E2 (UbCH12), E3 // IsopepƟdase [40,41] Others UBLs: ATG12, FAT10, MNSFβ, UFM1, URM, UBL5, SUMO4 [34][35][36][37][38] ModificaƟon of Ub: Phospho-Ub and Acetyl-Ub PolyubiquiƟn chains: Branched chains PolyUb mixed chains (modified by SUMO, NEDD8, ISG15) [21][22][23][24][25] Nucleo Ɵdes [190,191] Poly (PARylaƟon) Glu Asp Poly(ADP-ribose)polymerases (PARPs) // Poly (ADP-ribose) glycohydrolase (PARG) [191] * Found in prokaryotes A Almost followed by a proline (1 [39,40]. NEDD8 also forms chains through one of its six Lys [41].…”
Section: Pdb: 1nddmentioning
confidence: 99%
“…Neddylation is a highly conserved process analogous to ubiquitination, in which specific E1, E2, and E3 enzymes constitute a post‐translational modification cascade to facilitate the conjugation of ubiquitin‐like protein NEDD8 (neural precursor cell expressed, developmentally downregulated 8) to targeted proteins (Enchev, Schulman & Peter, 2015). All of the cullin scaffolds within Cullin‐RING ligases (CRLs) share a similar cullin homology domain and carboxyl‐terminal neddylation site, thus becoming the largest substrate family of neddylated substrates, although there are still many noncullin substrates of neddylation E3 enzymes such as p53, Histone H4, and the ribosomal protein L11.…”
Section: Pathological Contributions Of the Ubiquitin–proteasome Systementioning
confidence: 99%
“…Structural analysis has confirmed that APP‐BP1 is one of the two subunits that constitute a heterodimeric NEDD8‐activating enzyme (NAE). Comparable to ubiquitin activation, NAE is crucial for the initiation of a neddylation cascade due to its capability to expose and activate the C‐terminus of NEDD8 (Enchev et al., 2015). Therefore, APP‐BP1 acts as a core stimulator of the ubiquitin–proteasome system as it can promote the activation of CRLs by playing the role of a neddylation E1 enzyme and initiating NEDD8 transfer.…”
Section: Pathological Contributions Of the Ubiquitin–proteasome Systementioning
confidence: 99%
“…One major difference between modification by ubiquitin and its relatives is, with the exception of SUMO, none form polymeric structures on the substrate, with poly-SUMO chains playing a small role in overall SUMO signaling. For further details we refer to a number of excellent reviews on this subject [33][34][35][36][37][38].…”
Section: Ubiquitin-like Modifiersmentioning
confidence: 99%